Genome Diversity and Signatures of Selection for Production and Performance Traits in Dromedary Camels - Bahbahani, Hussain; Musa, Hassan H.; Wragg, David; Shuiep, Eltahir S.; Almathen, Faisal; Hanotte, Olivier (Frontiers in Genetics, 2019)
Dromedary camels (Camelus dromedarius) are single-humped animals found throughout the deserts of Africa, the Arabian Peninsula and the southwest of Asia. This well-adapted species is mainly used for milk and meat production, although some specific types exhibit superior running performance and are used in racing competitions. However, neither performance nor production camels are bred under intensive genomic selection programmes with specific aims to improve these traits. In this study, the full genome sequence data of six camels from the Arabian Peninsula and the genotyping-by-sequencing data of 44 camels (29 packing and 15 racing) from Sudan were analysed to assess their genome diversities, relationships and candidate signatures of positive selection. Genome admixture and principle component analyses indicate clear geographic separation between the Sudanese and the Arabian Peninsula camels, but with no population-specific genetic distinction within populations. Camel samples from the Arabian Peninsula show higher mean heterozygosity (0.560 ± 0.003) than those from Sudan (0.347 ± 0.003). Analyses of signatures of selection, using pooled heterozygosity (Hp) approach, in the Sudanese camels revealed 176, 189 and 308 candidate regions under positive selection in the combined, packing and racing camel populations, respectively. These regions host genes that might be associated with adaptation to arid environment, dairy traits, energy homeostasis and chondrogenesis. Eight regions show high genetic differentiation, based on Fst analysis, between the Sudanese packing and racing camel types. Genes associated with chondrogenesis, energy balance and urinary system development were found within these regions. Our results advocate for further detailed investigation of the genome of the dromedary camel to identify and characterize genes and variants associated with their valuable phenotypic traits. The results of which may support the development of breeding programmes to improve the production and performance traits of this unique domesticated species.